Do the police really protect and serve the public? Police deviance and public cynicism towards the law in Nigeria - Akinlabi, Oluwagbenga (Criminology & criminal justice, 2016)
This study empirically examines the everyday problem of corrupt policing and other related abuses in Nigeria, and how these deviant behaviours engender public cynicism towards the law. In any democratic society, police officers are expected to be accountable for their actions and inactions. But the perennial problem in Nigeria is that the police are not accountable to anyone. The history of Nigeria policing is littered with accounts of deviance, malevolent attitudes towards the public and failures of the police organization in detecting or disciplining errant officers. Using a sample of 462 participants from a cross-sectional survey, this study examines whether actual or vicarious experiences of police deviance are likely to predict public cynicism towards the law. This current study corroborates previous assertions that the relationship between the police and the public in Nigeria is poor and that police deviance engenders cynicism towards the law. Implications for policymaking and law-abiding behaviour are discussed